2005
DOI: 10.1007/s00198-004-1821-0
|View full text |Cite
|
Sign up to set email alerts
|

A 1-year combined weight-bearing training program is beneficial for bone mineral density and neuromuscular function in older women

Abstract: Forty-eight community living women 66-87 years old volunteered to participate in a 12-month prospective, randomized, controlled, trial. The aim was to determine if a combined weight-bearing training program twice a week would be beneficial to bone mineral density and neuromuscular function. The participants were pairwise age-matched and randomly assigned to either an exercise group (n=24) or a control group (n=24). Twenty-one subjects in the intervention group and 19 in the control group completed the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 38 publications
4
112
2
3
Order By: Relevance
“…However, Engles et al (1998) reported that no significant differences in static balance were seen following aerobic dancing (60 minutes per time, 3 times per week) in intensity (50-70% HRmax) for elderly men and women. An improvement in leg muscle strength was also found in a study for improving the balance performance of elderly people (Islam et al, 2004;Englund et al, 2005). However, in this study, although leg muscle strength has improved, improvement of static balance was not seen.…”
Section: The Effect Of Exercise Intervention On Physical Performancesupporting
confidence: 53%
See 1 more Smart Citation
“…However, Engles et al (1998) reported that no significant differences in static balance were seen following aerobic dancing (60 minutes per time, 3 times per week) in intensity (50-70% HRmax) for elderly men and women. An improvement in leg muscle strength was also found in a study for improving the balance performance of elderly people (Islam et al, 2004;Englund et al, 2005). However, in this study, although leg muscle strength has improved, improvement of static balance was not seen.…”
Section: The Effect Of Exercise Intervention On Physical Performancesupporting
confidence: 53%
“…However, in this study, although leg muscle strength has improved, improvement of static balance was not seen. The reason seems to be that the subject's balanced capability baseline level was higher than in previous studies (Rikli and Edwards, 1991;Rooks et al, 1997;Englund et al, 2005). Differences in the age and previous activity levels of subjects may explain the difference of a subject's balanced capability baseline level.…”
Section: The Effect Of Exercise Intervention On Physical Performancementioning
confidence: 59%
“…Repeated strain of bones above the physiological limit might lead to injury or even bone fracture. Englund et al (2005) and other authors regard long-term weight-bearing training as the most suitable activity influencing the BMD. Vainionpää et al (2005) proved that this type of exercise not only affects the bone density but also improves its architecture.…”
Section: Type Intensity and Methods Of Exercisementioning
confidence: 98%
“…Nevertheless, there exist studies which did not prove effect of walking on the increase of BMD (Martyn-St James & Carroll, 2008). Exercise regimes encompassing a combination of weight-bearing, balance and coordination exercises but excluding jumping activities, improve BMD, enhance muscular strength and walking ability and thus reduce the risks of fall and suffering consequent fractures (Englund et al, 2005). According to Feskanich et al (2002), activities improving balance and flexibility significantly contribute to reducing the risks of fall, whereas heavy-load and resistance exercises enhance muscular strength and BMD.…”
Section: Type Intensity and Methods Of Exercisementioning
confidence: 99%
“…A aplicação de um programa de treinamento, em idosas, combinando alongamento, exercícios de equilíbrio e coordenação motora, proporcionou um significante aumento da DMO no triângulo de Wards (5,3%), trocânter (6,3%), coluna lombar (3,1%), e braços (1,5%), em relação ao grupo controle 31 . Também foram observados ossos mais fortes em idosas que participavam de aulas de ginástica recreacional 32 e em meninas praticantes de handebol 33 , quando comparadas aos respectivos pares não praticantes.…”
Section: Impacto De Programas De Intervenção Sobre O Tecido óSseounclassified